Design considerations for AlGaN-based UV LEDs emitting near 235 nm with uniform emission pattern. (24th March 2017) - Lapeyrade, Mickael; Glaab, Johannes; Knauer, Arne; Kuhn, Christian; Enslin, Johannes; Reich, Christoph; Guttmann, Martin; Mehnke, Frank; Wernicke, Tim; Einfeldt, Sven; Weyers, Markus; Kneissl, Michael
Abstract: The uniformity of emission from deep ultraviolet light emitting diodes (UV LEDs) is investigated. The AlGaN-based heterostructures of the UV LEDs emitting around 235 nm were grown by metalorganic vapor phase epitaxy on epitaxially laterally overgrown AlN/sapphire substrates. The impact of different device designs on the spatial distribution of the electroluminescence for a series of UV LEDs is studied. Due to the relatively high resistivities of n-AlGaN and p-AlGaN layers, ranging from 10 to 0.1 Ω cm as well as specific contact resistances approaching 1 Ω cm 2, the emission patterns revealed heavy current crowding at the mesa edges causing a drop of power in the center of the emitting area and an asymmetry towards the side of the bonding pad of the n-contact. Simple analytical models considering the transfer and the current spreading length could only qualitatively explain the observed emission pattern. Using a 3D electro-thermal simulation of the current spreading in the LEDs the experimentally observed emission pattern could also be quantitatively reproduced. Based on these findings the 3D electro-thermal simulation was employed to optimize the contact geometry of the deep UV LEDs in order to achieve a more uniform power distribution.